Rheological Evaluation of Polymer (Sav 10) For Polymer Flooding Applications - Salih, Talib A.; Sahi, Safaa Hussain; Hameed, Omar K. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Half of the oil production of the worldwide is a result  of the water flooding  project. But the main concern of this process is mobility control of the injected fluid, because the unfavorable mobility ratio leads to fingering effect. Adding polymer to the injection water increase the water viscosity, therefore, the displacement will be more stable and have a greater sweep efficiency.   Using of polymer flooding has received more attention these days. Polymer has great potential in the Middle East region, especially in reservoir with high temperature and salinity.   The main objective of this work is to show the effect of shear rate, salinity, temperature, polymer concentration on polymer viscosity and determine the target viscosity to further displacement experiments. Polymer solution was prepared with two types of water (fresh water, brine). The reason of using two types of water is the ability of polymer to prepare by fresh water or brine.   Results from this study show that as the shear rate increases, polymer viscosity decreases. Also, the results show that in spite of polymer viscosity decreased with increase in temperature and salinity, polymer (SAV 10) shows that high temperatures have less effect on its viscosity at the same shear rate and has a salinity resistant up 200000 ppm. As polymer concentration increase, polymer viscosity increase until reach the target concentration which can be used for displacement experiments. It was found that the target concentration with viscosity 6.99 cp is 2000 ppm, which is closest to reservoir viscosity.